Peningkatan kemampuan Guru dalam menyusun kelengkapan mengajar melalui In-House Training pada SDN 04 Lunang - Erlinawati Erlinawati (JPGI (Jurnal Penelitian Guru Indonesia), 2018)
As an elementary school, there are many obstacles faced by SD Negeri 04 Lunang, such as the difficulty of obtaining professional teachers. Therefore, it is necessary to improve in various fields, especially the improvement of the quality of Master. The purpose of this study is to improve the ability of teachers in preparing the completeness of teaching and determine the appropriate steps to improve the ability of teachers in preparing the completeness of teaching. With In-House Training, all teachers are expected to have sufficient knowledge, understanding and experience, especially in the preparation of teaching comprehensiveness, which includes the Annual Program (Prota), Semester Program (Promes) and Learning Implementation Plan (RPP) in addition to other supporting facilities such as syllabus, education calendar, teaching schedule and student list. The research was conducted at SD Negeri 04 Lunang. Data collection is done through questionnaire, observation and documentation. There is an increase in the ability of teachers in preparing the completeness of teaching after In-House Training stage 1, and each teacher showed significant improvement. In-House Training is one of the most effective patterns to improve Teacher's ability to develop teaching comprehensiveness.